PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA PEMBELAJARAN TEMATIK KELAS IV TEMA 6 SUBTEMA 1 DI SEKOLAH DASAR - Nila Sari; Indri Anugraheni (Universitas Negeri Medan, 2021)
Abstract: Development Of Android-Based Learning Media In Class IV Theme 6 Subtema 1 Thematic Learning In Basic School This study was conducted to determine the feasibility and stages of developing Android-based learning media in the fourth grade thematic learning theme 6 sub-theme 1 in elementary schools. The type of research used is Research and Development (R&D). The data collection technique used an instrument sheet for the evaluation of the validation results of material experts and media experts which was carried out by 2 material experts and 2 media experts. The data analysis technique used is descriptive qualitative and percentage with the results obtained, namely: the results of the material expert validation obtained a percentage of 96.4% with a very high interval, the results of the media expert's assessment obtained a percentage of 91.7% with a very high interval. Based on the results of the validation of material experts and media experts for developing Android-based learning media in thematic learning for class IV theme 6 sub-theme 1 in elementary schools, it is declared valid and feasible to be applied. Keywords: Learning Media, Android, Thematic Learning Abstrak: Pengembangan Media Pembelajaran Berbasis Android Pada Pembelajaran Tematik Kelas IV Tema 6 Subtema 1 Di Sekolah Dasar. Penelitian ini dilaksanakan bertujuan untuk mengetahui kelayakan dan tahapan pengembangan media pembelajaran berbasis Android pada pembelajaran tematik kelas IV tema 6 subtema 1 disekolah dasar. Jenis penelitian yang digunakan adalah Penelitian dan Pengembangan atau Research and Development (R&D). Teknik pengumpulan data menggunakan lembar instrumen penilaian hasil validasi ahli materi dan ahli media yang dilaksanakan oleh 2 ahli materi dan 2 ahli media. Teknik analisis data yang digunakan yaitu deskriptif kualitatif dan presentase dengan hasil yang diperoleh yaitu: hasil validasi ahli materi memperoleh presentase 96,4% dengan interval sangat tinggi, hasil penilaian ahli media memperoleh presentase 91,7% dengan interval sangat tinggi. Berdasarkan hasil validasi ahli materi dan ahli media pengembangan media pembelajaran berbasis Android pada pembelajaran tematik kelas IV tema 6 subtema 1 disekolah dasar dinyatakan valid dan layak untuk diterapkan. Kata Kunci: Media Pembelajaran, Android, Pembelajaran Tematik